1998
DOI: 10.1177/00957984980241002
|View full text |Cite
|
Sign up to set email alerts
|

Racial Ideology and Racial Centrality as Predictors of African American College Students' Academic Performance

Abstract: The study focuses on the relationship between racial identity and academic achievement for African American college students. The Multidimensional Model of Racial Identity (MMRI) was used to assess the relationship between racial centrality, racial ideology, and academic performance. A total of 248 participants were recruitedfrom a predominantly Black college and a predominantly White college and were administered the Multidimensional Inventory of Black Identity (MIBI) to assess their racial ideology and racia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
216
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(226 citation statements)
references
References 25 publications
10
216
0
Order By: Relevance
“…Black racial identity theory includes measures of how members of oppressed social groups (Black people in this case) liberate themselves from oppressive social identities and form new, positive ones. One item on the Nationalist subscale of the Black Racial Identity Scale suggests a direct connection between social identity and critical social analysis: "I believe that the world should be interpreted from a Black perspective" (Sellers, Chavous, & Cooke, 1998). Others (Ginwright & James, 2002) argue that a critical social analysis of internalized and external oppression heals the wounds of social oppression and marginalization.…”
Section: Resultsmentioning
confidence: 99%
“…Black racial identity theory includes measures of how members of oppressed social groups (Black people in this case) liberate themselves from oppressive social identities and form new, positive ones. One item on the Nationalist subscale of the Black Racial Identity Scale suggests a direct connection between social identity and critical social analysis: "I believe that the world should be interpreted from a Black perspective" (Sellers, Chavous, & Cooke, 1998). Others (Ginwright & James, 2002) argue that a critical social analysis of internalized and external oppression heals the wounds of social oppression and marginalization.…”
Section: Resultsmentioning
confidence: 99%
“…They suggest that not only feelings of "connectedness" to the identity group and "awareness of racism" but also "embedded achievement"-"beliefs that achievement is a goal that is valued by the ingroup and therefore provides a specific goal (such as doing well in school) for motivation derived from the desire to enact group identity," (page 98)-will lead to higher academic achievement. Sellers, Chavous and Cooke (1998) find that among those students who maintain a salient and central racial identity, those who hold a "minority" ideology or beliefs of themselves as members of one of several subordinated groups in U.S. society have significantly higher grade point averages than those with assimilationist or nationalist ideologies.…”
Section: Identity Formation and Variation Within Groupsmentioning
confidence: 86%
“…Research on African American student persistence has found that prejudice, racism, and discrimination can negatively impact a student's commitment to his or her institution (Sellers, Chavous, & Cooke, 1998;Shelton & Sellers, 2000;Steele, 1997;Steele & Aronson, 1995). This impact negatively affects students' ability to negotiate the environment both academically and socially.…”
Section: The Black Doctoral Student Experiencementioning
confidence: 99%